The Influence of Customer Orientation and Marketing Digitalization on Educational Service Performance In The Era of Technological Disruption - Suriyanti, Erva; Afifah, Nur; Mustaruddin, Mustaruddin (Dinasti Publisher, 2025)
The development of digital technology in the era of technological disruption requires educational institutions to continue to adapt and innovate. This development triggers the need for adjustments in the performance of educational services, so it is important to understand the factors that influence this performance. This study aims to examine the effect of customer orientation and marketing digitalization on the performance of educational services in the era of technological disruption. This study applies a quantitative method by collecting data from a questionnaire. The population consists of all formal educational institutions that provide primary and secondary education, with a sample of 109 respondents taken randomly. The data was then analyzed using path analysis with the help of SPSS. The results of the study indicate that customer orientation and marketing digitalization have a positive and significant effect on the performance of educational services. The implementation of effective digital marketing strategies and efforts to meet customer needs and expectations can improve customer satisfaction and the image of the institution. Ultimately, this contributes to improving the performance of educational services. These findings conclude that educational institutions need to adopt a more customer-focused approach and make maximum use of digital technology in order to remain relevant and competitive in this increasingly developing era.